Cryospheric Hydrometeorology Observation in the Hulu Catchment (CHOICE), Qilian Mountains, China - Han, C. (2020)
Understanding cryospheric hydrology and the effects of cryospheric changes on river runoff is critical for sustainable water management especially in arid inland river basins such as those in northwest China where water resources mainly come from alpine areas. A cryospheric hydrometeorology observation system (CHOICE) has been established since 2008 in the Hulu catchment, which is a well‐instrumented experimental and representative catchment in the upper reaches of the inland Hei River, Qilian Mountains, northwest China. The CHOICE includes dense meteorological measurements from 2980 to 4800 m asl (e.g. glacier, snow, and permafrost hydrology) and water and heat balance in the vertical landscape zones including alpine grassland, meadow, shrub, coniferous forest, marshy meadow, and moraine‐talus zones. The comprehensive long‐term observations available for the CHOICE provide the basis for model development and application in cryospheric hydrological research. We focus on cryospheric hydrometeorological process of precipitation, freeze–thaw cycle, energy balance, soil–vegetation–atmosphere transfer (SVAT), runoff, groundwater reservoir, and hydrological resiliency within vertical elevation in CHIOCE.